PERAN INTERNATIONAL ORGANIZATION FOR MIGRATION (IOM) TERHADAP IMPLEMENTASI KEBIJAKAN INDONESIA DALAM PENYELENGGARAAN HAK PENDIDIKAN PENGUNGSI ANAK (KOTA PEKANBARU) - Berliana Ifada; M. Saeri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
IOM is part of the United Nations (UN) system as an intergovernmental organization engaged in migration. IOM is dedicated to advancing humane and orderly migration. IOM works to promote international cooperation on migration issues, help find practical solutions to migration problems, and provide humanitarian assistance to migrants in need. The aim of the researchers was to find out the role of IOM in implementing the right to education for child refugees in Pekanbaru City. This research is based on the theory of the role of international organizations according to Andre H. Pareira, which contains international organizations as initiators, facilitators, and mediators. Data was collected using qualitative methodology and interviews as a source of information, most of the data was published on IOM's official website, books, journals, official documents relating to the implementation of the right to education for child refugees. The results showed that IOM played a role in providing educational assistance to child refugees in Pekanbaru. IOM as a facilitator, namely IOM provides teachers in refugee ccommodation, IOM provides learning facilities for child refugees. In addition, IOM also produces an annual report on refugee education. Keywords: Refugees, IOM, Education.